KONSEP ADMINISTRASI KURIKULUM DALAM PERSPEKTIF AL-QUR’AN DAN HADIS - Muhamad Ardiansyah; Areefa Zahira Putri; Ahmad Zainuri; Frika Fatimah Zahra (CV. Adiba Aisha Amira, 2025)
This article explores the Concept of Curriculum Administration in the Perspective of the Qur’an and Hadith as an effort to understand how curriculum management in Islamic education should be grounded in divine values. Curriculum administration is not merely viewed as a technical activity encompassing planning, organizing, implementation, and evaluation, but also as a spiritual process oriented toward shaping a holistic human being knowledgeable, faithful, and virtuous. Based on a literature review of primary sources such as the Qur’an and Hadith, as well as contemporary academic references, it is found that the principles of curriculum administration in Islam include the values of tawhid (monotheism), justice, consultation (shura), trust (amanah), and diligence (itqan). These principles serve as the foundation for every stage of curriculum management to align with the goals of Islamic education, namely the realization of insan kamil—the complete human being capable of fulfilling the role of vicegerent (khalifah) on earth. Thus, curriculum administration grounded in divine revelation is expected to produce an educational system that is effective, character-based, and imbued with spiritual value.